Rumah Betang, Pintu Masuk Gereja ke dalam Budaya Kalimantan - Adi, Fransiskus Anang; Simatupang, Edwind Satri (Perspektif, 2020)
The Rumah Betang (Betang House) in the Dayak community in Kalimantan is a legacy of a communal culture. This community life of the local people expresses the high social values, unity, togetherness, peace, religiosity, and morality. In this article the writers attempt to discuss the relationship between Rumah Betang culture and the values of the Catholic faith. First of all, a description of the noble values of the Dayak people is given in the lifestyle in the Rumah Betang. Then, it describes the way of life of the Dayak people who have been baptized into the Catholic Church. The authors show how the noble values of the Rumah Betang culture have in common with the teachings of the Catholic faith, especially the communion of God’s people. In short, the writers believe that the Rumah Betang culture is the entrance for the Church to the very heart of the Dayak community.